The Ordinary Legislative Procedure in a Post-Brexit EU: The Case of Social Europe - Copeland, Paul (2021)
This article assesses the political and power dynamics of the Ordinarily Legislative Procedure (OLP) in social Europe and the likely impact of the UK’s departure in the field for future integration. It provides a detailed analysis of the OLP in social Europe during two recent periods of integration in the field—the first Barroso Commission (2004–2009) and the Juncker Commission (2014–2019). It finds the dynamics of the OLP have shifted from intergovernmental deadlock during the Barroso Commission to the characteristics of a new intergovernmental core state power during the Juncker Commission, even though the policy area is not a core state power per se. Despite the use of qualified majority voting policy agreements can only be achieved when there is near unanimity support in the Council, the Commission remains a neutral broker, and the Parliament shifts its position to that of the Council. As a result, continued opposition to integration in social Europe by Northern and Eastern Members means the removal of UK political agency will have only a marginal impact on the slow and piecemeal approach to integration in the field.